Peran Pemerintah dalam Pelestarian Kesenian Ludruk di Surabaya - Putra Desvanda Arya; Hertati Diana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Ludruk is a native East Javanese folk art originating from Jombang, but is also a typical Surabaya cultural mascot. Ludruk is a traditional drama performed by an arts group on a stage based on stories about people's daily lives. Ludruk art is part of East Java's rich and unique cultural heritage. Its preservation is important to maintain local cultural identity which can be a valuable asset for the community, due to the threat of loss and extinction. Ludruk is not only an artistic performance, but is also part of social life and preserving the community's identity can help strengthen a sense of solidarity and pride in local culture. . By choosing this topic, researchers can make a meaningful contribution to efforts to preserve and promote the desirability of ludruk art for the future. This research method is descriptive qualitative by collecting primary data through in-depth interviews and observations from related informants. Based on the research results that: 1. The role of the Surabaya City Culture, Youth and Sports and Tourism Department (Disbudporapar) as a regulator, plays a significant role in supporting arts and cultural activities in the preservation of ludruk art, ensuring that this traditional art remains alive and growing among young generation in ASPK policy.2. The role of the Department of Culture, Youth and Sports and Tourism of the City of Surabaya (Disbudporapar) as a facilitator, currently there is still a lack of support and facilities, allowing regeneration, regeneration of ludruk artists to be slow, competition with modern media, limited training: training programs are often undirected and inconsistent. 3. The role of the Department of Culture, Youth and Sports and Tourism of the City of Surabaya (Disbudporapar) as a dynamist, has been running well, but the current condition is that many ludruk groups in Surabaya have arts registration marks (TDK) and are registered at Disbudporapar. However, many of them have already died and Ludruk performances currently only rely on invitations from the Surabaya City Youth and Sports Culture Service (Disbudporapar).